In Vitro Cytotoxicity and Antioxidant Studies of Dovyallis caffra-Mediated Cassiterite (SnO2) Nanoparticles - Jerry O. Adeyemi (MDPI AG, 2023)
Many medicinal plants found in Africa, such as Dovyallis caffra, have been reported to contain various bioactive compounds, which have been found to reduce metal salts into their corresponding metal-based nanoparticles. In this paper, the evaluation of synthesis, characterization, and biological properties of Dovyallis caffra-mediated cassiterite (SnO2) nanoparticles was carried out. The physicochemical properties of the synthesized material were investigated using X-ray diffraction (XRD), energy dispersive X-ray analysis (EDX), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) techniques. The characterization studies revealed that the material possessed a single tetragonal cassiterite SnO2 phase, having a cluster-like foam appearance and an irregular spherical morphology with diameters ranging from 6.57 to 34.03 nm. The biological screening revealed that the prepared cassiterite (SnO2) nanoparticles exhibited cytotoxicity against the MCF-7 breast cancer cells, with an IC50 value of 62.33 µg mL−1, better than the standard drug 5-fluorouracil, with an IC50 value of 71.21 µg mL−1. The radical scavenging potential of the nanoparticles, using the DPPH assay, showed that it possessed a slightly better activity than ascorbic acid, a common antioxidant. These results suggest that the Dovyallis caffra-mediated cassiterite (SnO2) nanoparticles possess the potential to simultaneously generate and scavenge excess ROS, which in turn results in the exhibition of good cytotoxicity and antioxidant properties.